2000
DOI: 10.1023/a:1009217400140
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: A complete set of paint probes, with each probe specific for a single type of dog chromosome, was generated by DOP-PCR amplification of flow-sorted chromosomes. These probes have been assigned to high-resolution G-banded chromosomes of the dog and Arctic fox by fluorescence in-situ hybridization. On the basis of these results we propose improved nomenclature for the G-banded karyotypes of the dog and Artic fox. A comparative map between the Arctic fox, red fox and dog has been established based on results from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…The dog and fox, however, have very different karyotypes, the dog having 78 mostly acrocentric chromosomes, whereas the red fox has 34 metacentric chromosomes [42,43]. The cytological relationship between the dog and fox genomes is well understood: cytogenetic methods [44-47] and alignment of the fox meiotic map against of the dog genome [34] have demonstrated that most fox chromosomes correspond to two or three canine chromosomes. The canine genome sequence assembly CanFam2 was used to localize fox sequencing reads and contigs in the dog genome.…”
Section: Discussionmentioning
confidence: 99%
“…The dog and fox, however, have very different karyotypes, the dog having 78 mostly acrocentric chromosomes, whereas the red fox has 34 metacentric chromosomes [42,43]. The cytological relationship between the dog and fox genomes is well understood: cytogenetic methods [44-47] and alignment of the fox meiotic map against of the dog genome [34] have demonstrated that most fox chromosomes correspond to two or three canine chromosomes. The canine genome sequence assembly CanFam2 was used to localize fox sequencing reads and contigs in the dog genome.…”
Section: Discussionmentioning
confidence: 99%
“…Tree topology for Carnivora is modified from Eizirik et al (2010). Published chromosome painting data for Felidae (Wienberg et al , 1997; Yang et al , 2000; Tian et al , 2004), Hyaenidae and Viverridae (Perelman et al , 2005), Herpestidae and Eupleridae (Nash et al , 2008), Canidae (Breen et al , 1999b; Yang et al , 1999, 2000; Graphodatsky et al , 2000a, 2001, 2008; Nash et al , 2001; Nie et al , 2003), Mephitidae (Perelman et al , 2008), Mustelidae (Hameister et al , 1997; Cavagna et al , 2000; Graphodatsky et al , 2000b, 2002; Nie et al , 2002), Procyonidae (Nash et al , 2008; Perelman et al , 2008), Ailuridae (Nie et al , 2002; Tian et al , 2002), Phocidae (Frönicke et al , 1997), Ursidae (Nash et al , 1998, 2001; Tian et al , 2004; Yang and Graphodatsky, 2004) and the data in this study were used for this figure. The ACK was from Murphy et al (2001a).…”
Section: Figurementioning
confidence: 99%
“…During the last two decades, chromosome-specific painting probes have been made for nine carnivores: the domestic cat ( Felis catus , FCA) (Wienberg et al , 1997), the domestic dog ( Canis familiaris , CFA) (Breen et al , 1999a; Yang et al , 1999; Graphodatsky et al , 2000a), the red fox ( Vulpes vulpes , VVU) (Yang et al , 1999), the Japanese raccoon dog ( Nyctereutes procyonoides , NPR) (Nash et al , 2001), the American mink ( Mustela vision , MVI) (Graphodatsky et al , 2002), the stone marten ( Martes foina , MFO) (Nie et al , 2002), the giant panda ( Ailuropoda melanoleuca , AME) (Nash et al , 1998), the striped skunk ( Mephitis mephitis , MME) and the hooded skunk ( Mephitis macroura , MMA) (Perelman et al , 2008). A series of comparative chromosome maps have been established among carnivores, and karyotypic phylogenetic relationships in different carnivore groups have been revisited by chromosome painting (Nash et al , 1998, 2001, 2008; Graphodatsky et al , 2000a, 2001, 2002, 2008; Nie et al , 2002; Tian et al , 2004; Perelman et al , 2005, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations